Synovial Sarcoma of the Female Genital Tract: A Protean Mimic of Müllerian Neoplasia. (November 2020) - Kolin, David L.; Crum, Christopher P.; Baranov, Esther; Cin, Paola Dal; Chang, Martin C.; Colgan, Terence J.; Dickson, Brendan C.; Hornick, Jason L.; Nucci, Marisa R.
Abstract : Synovial sarcoma most commonly occurs in the extremities but has rarely been described in the female genital tract. In this series, we describe the clinical, morphologic, immunohistochemical, and molecular features of 7 cases of vulvovaginal synovial sarcoma (vulva, n=6; vagina, n=1). We emphasize their wide morphologic spectrum, which can overlap significantly with other more common tumors at these sites, as highlighted by 2 cases initially diagnosed as other entities (endometrioid carcinoma and malignant peripheral nerve sheath tumor). The average patient age was 41 (range: 23 to 62) years and tumor size ranged from 0.8 to 7 cm. Histologically, the tumors were biphasic (n=6) and monophasic (n=1). All cases were confirmed with fluorescence in situ hybridization or sequencing, and 5/5 cases were positive for the novel immunohistochemical markers SSX and SS18-SSX. In 3 cases with follow-up, 2 patients died of disease and 1 was alive with no evidence of disease. Previously described cases arising in the female genital tract are also reviewed. Vulvovaginal monophasic synovial sarcoma raises a broad differential diagnosis, including smooth muscle tumors, spindled carcinomas, and melanoma. Biphasic synovial sarcoma may mimic Müllerian carcinosarcoma, endometrioid carcinoma with spindled, corded, and hyalinized elements, and mesonephric-like adenocarcinoma. Awareness that synovial sarcoma can occur in the female genital tract with a wide variety of histologic appearances is critical for correctly diagnosing this rare entity. In particular, synovial sarcoma should be considered for any deeply situated "adenocarcinoma" in the vulva, with attention to subtle spindle cell differentiation.